The pattern of intravenous proton-pump inhibitor utilization at an academic medical center in Riyadh, Saudi Arabia - Yahya Ali Mohzari; Ahmed Alsaegh; Syed Mohammed Basheeruddin Asdaq; Sulafah N Al Shanawani; Amani A Albraiki; Amal Bagalb (Wolters Kluwer Medknow Publications, 2020)
Objective: This study was designed to evaluate the extent of inappropriate utilization of intravenous proton-pump inhibitors (IV-PPIs) and its financial burden in a Middle Eastern tertiary care university hospital. Methods: This was an observational, retrospective, cross-sectional study carried out in King Saud University Medical City, Riyadh, Saudi Arabia. During a study period of 6 consecutive weeks, all hospitalized adult patients (age ≥18) who received IV-PPI selected and mapped with their indications. The patient indications analyzed in comparison with the appropriate indications developed based on the evidence from published literature and guidelines. Findings: A total of 347 patients were identified, with a mean age of 51.5 years, of which 51.9% were male. Of all the patients who received IV-PPIs, 251 (72.3%), 66 (19%), and 30 (8.7%) received for stress ulcer prophylaxis (SUP), peptic ulcer disease (PUD) or gastroesophageal reflux diseases (GERDs), and upper gastrointestinal bleeding, respectively. Overall, only 110 (31.7%) of the 347 patients received IV-PPIs appropriately. The patients with SUP showed the highest percentage of inappropriate use of IV-PPI (80.59%) compared to PUD/GERD (19%). The total cost of inappropriate prescription of IV-PPI was 585,167 Saudi Riyal (SAR) (156,044 USD). Conclusion: There is a high tendency of IV-PPI's inappropriate prescription in our hospital setting. This large-scale inappropriate prescription of IV-PPI in the hospital setting not only may lead to increased financial burden but also expose patients to number of undesired effects.